Coast : A Celebration of Britain's Coastal Heritage - Somerville, Christopher; Edited by Wallis, Clare (London BBC Worldwide Limited, 2005)
Accompanying the BBC series, Coast is not only a superbly illustrated celebration of Britain's coastal areas but a practical guide to all that they have to offer.
Include Colour Illustrations and Index
Indexer by Swindells, Lynda
Keywords: Great Britain -- Coasts